Acute sleep restriction affects sport-specific but not athletic performance in junior tennis players - Vitale, J. A.; Bonato, M.; Petrucci, L.; Zucca, G.; La Torre, A.; Banfi, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Little is known about the effect of sleep restriction (SR) on different domains of athletes` physical performance. Therefore, the aim of this randomized, counterbalanced, and crossover study was to evaluate the effect of acute SR on sport-specific technical and athletic performance in male junior tennis players.